1984
DOI: 10.1111/j.1600-0609.1984.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

The myelodysplastic syndromes ‐ A study of haemostatic function and platelet ultrastructure

Abstract: The myelodysplastic syndromes (MDS) are characterised by dysplastic marrow and cytopenia. Clinically detectable bleeding is uncommon and usually attributed to thrombocytopenia. We have investigated some aspects of haemostatic function in 17 patient5 with MDS and compared the results with findings from 17 control patients matched for age and sex. No specific disorder of blood coagulation or fibrinolysis was identified. The main abnormalities observed in the patients were: prolongation of the bleeding time which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Recently, a detailed study of the clinical features of 2900 patients with MDS reported that even among patients with platelet counts of Ͼ50,000/l, 19% had signs of bleeding at the time of diagnosis (4). Taken together, these data suggest a platelet count-independent functional platelet defect in MDS, which is supported by sporadic reports indicating insufficient platelet aggregation (3,(5)(6)(7)(8). The existence of such a functional platelet defect may very well contribute to the high rate of hemorrhagic complications observed in patients with MDS.…”
mentioning
confidence: 64%
“…Recently, a detailed study of the clinical features of 2900 patients with MDS reported that even among patients with platelet counts of Ͼ50,000/l, 19% had signs of bleeding at the time of diagnosis (4). Taken together, these data suggest a platelet count-independent functional platelet defect in MDS, which is supported by sporadic reports indicating insufficient platelet aggregation (3,(5)(6)(7)(8). The existence of such a functional platelet defect may very well contribute to the high rate of hemorrhagic complications observed in patients with MDS.…”
mentioning
confidence: 64%
“…The initial research in this field goes back to 1969, when Caen et al [11] studied platelet function in 7 patients with RA. Since 1984, several studies have concluded that there is no strong association between impaired aggregation and hemorrhagic events [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Bleeding manifestations are relatively rare in patients with idiopathic thrombocytopenic purpura (ITP) as compared with equally thrombocytopenic patients with megakaryocyte deficiency. Hemorrhage may occur at apparently acceptable platelet levels in various thrombocytopenic patients, probably due to associated platelet dysfunction [4][5][6][8][9][10][11][12]. It is difficult to evaluate platelet functions in patients with thrombocytopenia and no routine method has been described for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data suggest that platelet functional capacity and consequently bleeding risk are heterogeneous in various causes of thrombocytopenia [4][5][6][7]. Bleeding manifestations are relatively rare in patients with idiopathic thrombocytopenic purpura (ITP) as compared with equally thrombocytopenic patients with megakaryocyte deficiency.…”
Section: Introductionmentioning
confidence: 99%